A chemosensor for micro- to nano-molar detection of Ag+ and Hg2+ ions in pure aqueous media and its applications in cell imaging. Issue 41 (9th October 2017) - Nandre, Jitendra P.; Patil, Samadhan R.; Sahoo, Suban K.; Pradeep, Chullikkattil P.; Churakov, Andrei; Yu, Fabiao; Chen, Lingxin; Redshaw, Carl; Patil, Ashok A.; Patil, Umesh D.
Abstract : The synthesis and characterization of a simple thiourea-based Ag + and Hg 2+ sensor is reported. Abstract : The pyridine substituted thiourea derivativePTB-1 was synthesized and characterized by spectroscopic techniques as well as by single crystal X-ray crystallography. The metal ion sensing ability ofPTB-1 was explored by various experimental (naked-eye, UV-Vis, fluorescence, mass spectrometry and 1 H NMR spectroscopy) and theoretical (B3LYP/6-31G**/LANL2DZ) methods.PTB-1 exhibited a highly selective naked-eye detectable color change from colorless to dark brown and UV-Vis spectral changes for the detection of Ag + with a detection limit of 3.67 μM in aqueous medium. The detection of Ag + ions was achieved by test paper strip and supported silica methods. In contrast, PTB-1 exhibited a 23-fold enhanced emission at 420 nm in the presence of Hg 2+ ions with a nano-molar detection limit of 0.69 nM. Finally, the sensorPTB-1 was applied successfully for the intracellular detection of Hg 2+ ions in a HepG2 liver cell line, which was monitored by the use of confocal imaging techniques.